PERSPEKTIF HISTORIS CAMPURSARI DAN CAMPURSARI ALA MANTHOU’S - Joko Tri Laksono (Imaji, 2010)
Campursari is an ensemble of a highly and aesthetically musical taste of various musical instruments, each of wich has distinctive characteristics and playing patterns. The problems arising from the difference in the system of notation and harmony can be overcome in so far each, musician is aware of the importance of togetherness needed in the musical performance. In history instrumentation of campursari cannot leave karawitan and music keroncong which represents beginning at first merger from bath the ensembles. Manthou’s as originators campursari tries to alli the instrumentation becames one fully unity especially about its tune. Kata kunci: musik campursari, perspektif historis